2012
DOI: 10.1177/1045159512452262
|View full text |Cite
|
Sign up to set email alerts
|

Adult Learners and AIDS Artwork

Abstract: Significant stigma exists to marginalize

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Our research regarding music and social learning also contributes to broader discussions regarding art-based and aesthetic adult education. This research has pointed to the power of art to facilitate education on social issues, including ecojustice, women's rights, and public health (Bell & Clover, 2017;Clover, 2015Clover, , 2018Collins, 2012). Additionally, Karafillidis (2012) argued that visual and musical arts could reinforce one another to enhance a learner's artistic appreciation.…”
Section: Facilitating Change Using Music and Visual Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research regarding music and social learning also contributes to broader discussions regarding art-based and aesthetic adult education. This research has pointed to the power of art to facilitate education on social issues, including ecojustice, women's rights, and public health (Bell & Clover, 2017;Clover, 2015Clover, , 2018Collins, 2012). Additionally, Karafillidis (2012) argued that visual and musical arts could reinforce one another to enhance a learner's artistic appreciation.…”
Section: Facilitating Change Using Music and Visual Artmentioning
confidence: 99%
“…Papadimitriou (2010) showed that visual art could enhance scientific learning in adults, particularly with regard to geography. Collins (2012) connected art education to public health by arguing that art can be used to reduce stigma related to living with HIV/AIDS.…”
Section: Facilitating Change Using Music and Visual Artmentioning
confidence: 99%